Right ventricular strain: measurement and clinical application. (September 2018) - Ayach, Bilal; Fine, Nowell M.; Rudski, Lawrence G.
Abstract : Purpose of review: Right ventricular (RV) assessment has long been challenging and technically difficult using echocardiography. This is mainly the result of the asymmetrical shape of the RV making it difficult to visualize on one-or-two dedicated views, thus requiring multiple integrated views and subjective assessment. Measurement of tricuspid annular systolic plane excursion and RV tissue Doppler velocity have become relied-upon methods of objective assessments; however, have limitations for characterizing true RV physiology. Recent findings: Studies suggest that two-dimensional RV free wall longitudinal systolic strain (RVFWS) using speckle-tracking echocardiography has emerged as a reproducible, feasible and highly prognostic technique for quantifying RV function. This has been demonstrated for patients with heart failure, ischemic heart disease, pulmonary hypertension, infiltrative disease and many other types of cardiovascular disease. Summary: The current review outlines the clinical use of RVFWS, and its integration with other commonly used echocardiographic measurements to more accurately assess RV function, cause and prognosis to guide and improve patient care decision making.